Digital image processing (DIP) and generative adversarial networks (GANS) techniques for improvement low-resolution face recognition - Kurnia, Dian Ade; Sudrajat, Dadang; Mohd, Othman; Abdollah, Mohd Faizal; Efendi, Dwi Marisa; Rahmatullah, Sidik (International Information and Engineering Technology Association, 2024)
This research addresses the challenge of improving the accuracy of face recognition in lowresolution images using Digital Image Processing (DIP) and Generative Adversarial Networks (GANs). Recent advances in facial recognition have achieved high accuracy, although predominantly for high-resolution images. Low-resolution images, common in surveillance and mobile devices, pose significant accuracy challenges. The proposed DIP+GAN method integrates image preprocessing techniques such as cropping, resizing, normalization, and filtering with GANs to enhance low-resolution images. The study leverages the Georgia Tech Face Database for experiments and employs various DIP techniques and GAN architecture. The results demonstrate improved facial recognition accuracy in low-resolution images and contribute significantly to the fields of digital image processing and artificial intelligence. This research highlights the importance of preprocessing in face recognition and the effectiveness of GANs in dealing with lowresolution images.